2021
DOI: 10.1016/j.metop.2021.100106
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in infectious complications in critically ill patients with or without COVID-19

Abstract: 25-hydroxyvitamin D [25(OH)D] is an important immunomodulator, whose deficiency may aggravate the incidence and outcome of infectious complications in patients admitted to the intensive care unit. The most recognized extra-skeletal action of vitamin D is the regulation of immune function. Host defense against intracellular pathogens depends upon both innate and adaptive immunity. It has been suggested that vitamin D regulates the pro-inflammatory endothelial response to lipopolysaccharide, rendering it a role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“…Vitamin D deficiency is highly prevalent across all age groups and countries [ 80 ]. Although vitamin D deficiency was further determined to be associated with greater illness severity (also in patients with COVID 19), a causal relationship between vitamin D deficiency and multiple organ dysfunction has not been established [ 81 , 82 , 83 , 84 ]. Thus, the efficacy of vitamin D as a therapeutic in critically ill patients remains controversial [ 85 ].…”
Section: Supplementation With Specific Nutrientsmentioning
confidence: 99%
“…Vitamin D deficiency is highly prevalent across all age groups and countries [ 80 ]. Although vitamin D deficiency was further determined to be associated with greater illness severity (also in patients with COVID 19), a causal relationship between vitamin D deficiency and multiple organ dysfunction has not been established [ 81 , 82 , 83 , 84 ]. Thus, the efficacy of vitamin D as a therapeutic in critically ill patients remains controversial [ 85 ].…”
Section: Supplementation With Specific Nutrientsmentioning
confidence: 99%
“… 13 It was primarily recognized for supporting bone health through calcium homeostasis, but recently, it has drawn attention to its critical role in modulating immune cells and inhibiting the inflammatory response. 14 Previous studies have indicated a relationship between vit D deficiency and some cancers, 15 certain autoimmune, 16 and infectious viral diseases such as SARS, MERS, and Influenza A. 17 In addition, there is evidence that vit D supplementation effectively decreases the level of proinflammatory cytokines such as TNF‐α and IL‐6, stimulates anti‐inflammatory cytokines such as IL‐10 and IL‐12, 3 and reduces the rate of ICU admission of COVID‐19‐infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also highlight that vitamin D plays an important role in infectious diseases ( 19 , 20 ). The overall effect of vitamin D deficiency in infections is associated with alteration of the critical immune response such as genetic expression related to antioxidants, cytokine storm, metabolism, and cellular function ( 21 ). However, there are arguments that vitamin D does not do much for infections.…”
Section: Introductionmentioning
confidence: 99%